Effects of rewards and pedometer-feedback on children’s physical activity: a school-based intervention study - Allafi, Ahmad R (Progress in Nutrition, 2020)
Background: Current prevalence estimates for child obesity in Arabian Gulf countries are some of the world’s highest. The study aims to evaluate the effect of rewarding and pedometer- feedback on increasing the children’s physical activity and decrease obesity rates. Methods: A sum of 225 participants (110 boys - 115 girls) ranging from 9 to 11 years old from six public elementary schools in Kuwait City, Kuwait took part in the study. Three different groups were created; feedback (FB), feedback with rewards (FD+R), and control group (C). Children were assigned to one of the three groups randomly. In the FB group, participants received information about the function of pedometer only wherein the FB+R group received information about the function of the pedometer and were asked for a 3000 counts milestone to get ten stickers. The control group participants haven’t received any information about the function of the pedometer. Pedometer counts were taken from all participants through five physical education classes. Results: The average step counts for the groups were; 2091±483 for the control group, 2655±577 for the FB group, and 3429±458 for the FB+R group. A significant difference was found in the counts among the three groups (p < 0.05). Post-hoc Tuky analysis indicated a specific significant difference between the FB+R group and the two other groups (P < 0.00). Conclusion: The results of the study showed that encouraging children with rewards will sustainably increase theirphysical activity.